Liquid metal-based core-shell structure phase change filler as well as preparation method and application thereof
通过在液态金属基核壳结构相变填料中使用多孔材料和纳米成核剂,并以氧化石墨烯包裹,解决了液态金属相变材料的漏液和过冷问题,实现了高稳定性和高 Thermal conductivity, suitable for temperature regulation and energy storage applications.
Patent Information
- Application Number
- CN202411368677.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-03
AI Technical Summary
Existing liquid metal phase change materials are prone to liquid leakage and supercooling, and existing fixed phase change composite and microencapsulation methods are difficult to improve stability and thermal conductivity at the same time.
Porous materials are used as a carrier to fill liquid metal and nanonucleation agents, and wrapped with graphene oxide material to form a core-shell structure. The liquid metal-based core-shell structure phase change filler is prepared by solvent volatilization method to improve structural stability and thermal conductivity.
It realizes high stability, low supercooling and high thermal conductivity of liquid metal phase change materials, effectively prevent liquid leakage and improve supercooling, and is suitable for temperature regulation and energy storage fields.
Smart Images

Figure CN119242272A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of new materials, and relates to a liquid metal-based core-shell structure phase change filler and a preparation method and application thereof, and specifically relates to a liquid metal-based core-shell structure phase change temperature regulating filler with high stability, low supercooling and high thermal conductivity and a preparation method and application thereof. Background Art
[0002] Phase change materials (PCMs) can store a large amount of latent heat during the phase change process and are often used in solar energy collection, building air conditioning, battery and electronic equipment temperature control thermal management. At present, PCMs that can meet the needs of practical applications need to have the following properties: suitable phase change temperature range, high phase change latent heat and specific heat capacity, high thermal conductivity before and after the phase change; small volume change before and after the phase change, appropriate crystallization rate, good thermal and chemical stability, strong cycle durability, low degree of supercooling and good compatibility with the matrix material. Phase change materials are divided into solid-solid, solid-liquid, liquid-gas and solid-gas phase change materials according to the state of matter. Common solid-liquid phase change materials include paraffin, fatty acids, fatty alcohols and polyethylene glycol.
[0003] The above-mentioned organic phase change materials such as paraffin wax have low thermal conductivity and slow thermal response, making it difficult to achieve the purpose of transient cooling of electronic devices, which greatly limits the application of phase change materials in the field of electronic temperature control. Using liquid metal with high phase change latent heat and high thermal conductivity as phase change material is one of the effective strategies to achieve transient cooling. However, liquid metal has disadvantages such as large volume expansion coefficient and difficult nucleation. Liquid metal phase change materials are prone to leakage and serious overcooling, which is a key problem hindering their application.
[0004] The existing strategies for improving the stability of phase change materials mainly include: using shaped phase change composite materials and microencapsulation. In terms of reducing the supercooling of liquid metal, it is mainly through the introduction of nucleating agents such as copper and indium. Yao et al. used expanded graphite (EG, 5wt.%) as a medium to successfully prepare a stable phase change composite material (PCC) of octadecane and gallium that is difficult to mix directly [1]. Xu et al. prepared a shaped phase change composite material of foam carbon or foam copper loaded with liquid metal. The foam copper provides an additional thermal conductivity pathway and constructs a thermal conductivity network to obtain a higher thermal conductivity and low supercooling [2]. Due to the large volume change of liquid metal during phase change, the improvement of the leakage prevention of liquid metal for shaped composite phase change materials that rely on microporous adsorption to fix the phase change material is very limited.
[0005] Blaiszik et al. prepared gallium-indium (Ga-In) core-shell microcapsules using an in-situ urea-formaldehyde (UF) microencapsulation method and studied the control process of capsule size, shape, thermal properties and shell thickness [3]. In addition, Raj et al. proposed the use of an in-situ polymerization method to prepare nano-gallium capsules (n-Ga) and explored the energy storage performance of microcapsule-based phase change materials [4]. However, the volume expansion coefficient of liquid metal phase change is quite different from that of the shell material. The high internal stress during phase change causes the shell material to easily rupture and leak. Therefore, there is still a lack of effective strategies to prepare liquid metal phase change materials with high stability and low supercooling.
[0006] References
[0007] [1]Y.Yao,Y.Cui,ZJRaDeng,Phase change composites of octadecane andgallium with expanded graphite as a carrier,12(27)(2022)17217-17227.
[0008] [2]Z.Xu,X.Li,Z.Zhu,Q.Wang,Y.Chen,TJECMa,Management,Experimental study on the heat transfer performance of a gallium heat sink,213(2020)112853.
[0009] [3] B. Blaiszik, A. Jones, NRSottos, SRJ Jom White, Microencapsulation of gallium–indium (Ga–In) liquid metal for self-healing applications, 31 (4) (2014) 350-354.
[0010] [4]CRRaj,S.Suresh,R.Bhavsar,VKSingh,SJTAReddy,Effect of nano-galliumcapsules on thermal energy storage characteristics of manganeseorganometallic SS-PCM,680(2019)178341. Summary of the invention
[0011] The technical problem to be solved by the present invention is that liquid metals with high phase change latent heat and high thermal conductivity in the prior art are prone to leakage and supercooling. Existing methods such as fixed phase change composite and microencapsulation are difficult to solve the above problems at the same time. To address this technical difficulty, the present invention uses porous materials as carriers to fill liquid metal and nano-nucleating agents, and then wraps the surface with graphene oxide materials with high flexibility, density and strength, so as to achieve the preparation of high stability and low supercooling liquid metal phase change materials.
[0012] Invention concept: The liquid metal-based core-shell structure phase change filler prepared by the solvent volatilization method provided by the present invention is a core-shell structure; wherein, (1) core material: the porous granular material has a porous structure inside, and the porous granular material is used as a carrier to load liquid metal and nano nucleating agent. The porous granular material has a large loading capacity and the porous structure plays a supporting role, which can improve the structural stability; at the same time, the liquid metal provides high phase change latent heat and high thermal conductivity, and the nano nucleating agent can effectively improve the supercooling of the liquid metal; (2) shell material: the shell material is divided into two layers: ① the inner shell layer is a driving agent, a driving molecule represented by benzotriazole (BZT), and the outer layer is graphene oxide; the benzotriazole ( BTA), 2-(2'-hydroxy-3',5'-dipentylphenyl)benzotriazole (BZT), etc. can provide driving force for the efficient coating of flexible graphene oxide because they can undergo physical and chemical adsorption on the surface of graphene oxide. At the same time, BTA, BZT, etc. can also give the filler anti-ultraviolet aging and anti-corrosion properties; ② The graphene oxide in the outer shell layer has the advantages of high flexibility, high density, and high tensile strength. It can effectively seal liquid metals. At the same time, it can also effectively buffer the volume expansion stress generated when the buffered metal undergoes phase change and prevent leakage. Compared with traditional polymer shells, GO is only a single atomic layer thick, which can effectively improve thermal conductivity.
[0013] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0014] The present invention discloses a liquid metal-based core-shell structure phase change filler, characterized in that it comprises a core, an inner shell and an outer shell;
[0015] Wherein, the core is a porous material, and the core is used as a carrier to load the liquid metal and the nano nucleating agent;
[0016] The inner shell is coated on the outer surface of the inner core, and the inner shell is a driving agent;
[0017] The outer shell is coated on the outer surface of the inner shell, and the outer shell is graphene oxide.
[0018] In some embodiments, the porous material is any one of mesoporous silica and porous carbon or a combination of two thereof; the liquid metal is any one of gallium, indium, bismuth, cesium and rubidium or a combination thereof; the nano nucleating agent is any one of nano copper, nano silver, nano magnesium oxide, nano aluminum oxide and nano silicon oxide or a combination thereof; the driving agent is any one of benzotriazole and 2-(2'-hydroxy-3',5'-dipentylphenyl)benzotriazole or a combination thereof.
[0019] Wherein, the abbreviation of the benzotriazole is BTA; the abbreviation of the 2-(2'-hydroxy-3',5'-dipentylphenyl)benzotriazole is BZT.
[0020] Furthermore, the present invention discloses a method for preparing the above-mentioned liquid metal-based core-shell structure phase change filler, comprising the following steps:
[0021] (1) mixing liquid metal, nano-nucleating agent and porous material, and grinding to obtain a porous material loaded with liquid metal and nano-nucleating agent;
[0022] (2) dispersing the porous material loaded with liquid metal and nano nucleating agent obtained in step (1) and the driving agent in a volatile solvent, and mixing them to obtain a mixture A;
[0023] (3) preparing a graphene oxide solution; adding the graphene oxide solution to the first surfactant solution and mixing to obtain a mixture B;
[0024] (4) adding the mixture A obtained in step (2) to the mixture B obtained in step (3) under stirring, stirring and emulsifying, to obtain a mixture C;
[0025] (5) adding a second surfactant solution to the mixture C obtained in step (4), stirring under heating conditions to allow the volatile solvent to fully evaporate, separating the solid from the liquid, washing the solid, and drying to obtain a liquid metal-based core-shell structure phase change filler.
[0026] In some embodiments, the porous material is any one of mesoporous silica and porous carbon or a combination of two thereof; the liquid metal is any one of gallium, indium, bismuth, cesium and rubidium or a combination thereof; the nano nucleating agent is any one of nano copper, nano silver, nano magnesium oxide, nano aluminum oxide and nano silicon oxide or a combination thereof; the driving agent is any one of benzotriazole and 2-(2'-hydroxy-3',5'-dipentylphenyl)benzotriazole or a combination thereof.
[0027] In some embodiments, preferably, the porous material is any one of mesoporous silica and porous carbon or a combination of two; the liquid metal is any one of gallium and indium or a combination of two; the nano nucleating agent is any one of nano silver, nano magnesium oxide and nano aluminum oxide or a combination of several thereof; and the driving agent is benzotriazole.
[0028] The size of the porous material is between 1 μm and 1 mm, and the pore size is between 1 nm and 10 μm. Preferably, the size of the porous material is between 1 μm and 50 μm, and the pore size is between 20 nm and 3 μm. The porous material is subjected to surface hydrophobic treatment before use, that is, the surface is usually treated with small molecules such as silane coupling agent, oleic acid, etc., one end of which can react with surface functional groups and the other end is hydrophobic.
[0029] Wherein, when the porous material is mesoporous silica, the mesoporous silica is commercially available silica with surface oleic acid modified.
[0030] Wherein, the size of the nano nucleating agent is 1 nm to 1 μm, preferably 5 nm to 0.2 μm, and more preferably 5 nm to 0.1 μm.
[0031] In some embodiments, in step (1), the mass ratio of the liquid metal to the porous material is 1:10 to 10:1; the mass of the nano nucleating agent accounts for 0.1% to 1.0% of the mass of the liquid metal.
[0032] In some embodiments, preferably, in step (1), the mass ratio of the liquid metal to the porous material is (6-10):1, and more preferably (8-10):1; the mass of the nano-nucleating agent accounts for 0.1% to 0.6% of the mass of the liquid metal, and more preferably 0.2% to 0.5%, and even more preferably 0.2% to 0.4%, and most preferably 0.3%.
[0033] Among them, in step (1), a certain temperature is maintained during the grinding process in order to ensure that the liquid metal is in liquid state. The specific temperature is determined according to the melting points of different liquid metals. The temperature is higher than the melting point of the liquid metal to ensure that the liquid metal melts. The purpose of grinding is to allow the liquid metal and the nano-nucleating agent to be wetted, adsorbed and loaded in the porous material.
[0034] In some embodiments, in step (2), the volatile solvent is any one of dichloromethane, chloroform, xylene, acetone and dimethyl ether, or a combination of several of them; the driving agent is any one of benzotriazole and 2-(2'-hydroxy-3',5'-dipentylphenyl)benzotriazole, or a combination of two of them; the mass ratio of the porous material loaded with liquid metal and nano nucleating agent to the driving agent is 1:10 to 10:1.
[0035] In some embodiments, preferably, in step (2), the volatile solvent is dichloromethane; the driving agent is benzotriazole; the mass ratio of the porous material loaded with liquid metal and nano nucleating agent to the driving agent is (1-5):1, further preferably (1-3):1, and further preferably 2:1.
[0036] Among them, in step (2), when the amount of the porous material loaded with liquid metal and nano nucleating agent is 40 mg, the amount of the volatile solvent is 15 mL to 60 mL, that is, the mass volume ratio of the porous material loaded with liquid metal and nano nucleating agent to the volatile solvent is 40 mg: (15 mL to 60 mL), preferably 40 mg: (20 mL to 40 mL), and further preferably 40 mg: 30 mL.
[0037] Wherein, in step (2), the mixing is carried out by ultrasonic stirring for 10 minutes to 30 minutes to fully mix.
[0038] In some embodiments, in step (3), the first surfactant is any one of sodium dodecyl sulfate and sodium pentadecylbenzenesulfonate or a combination of both; in the first surfactant solution, the solvent is water, and the mass fraction of the first surfactant in the solution is 1% to 10%; in the graphene oxide solution, the solvent is water, and the concentration of graphene oxide in the solution is 1 to 13 g / L; in the mixture B, the mass of the first surfactant accounts for 3 to 12% of the mass of the graphene oxide.
[0039] In some embodiments, preferably, in step (3), in the first surfactant solution, the solvent is water, and the mass fraction of the first surfactant in the solution is 2% to 8%, further preferably 2% to 6%, and further preferably 4%; in the graphene oxide solution, the solvent is water, and the concentration of graphene oxide in the solution is 2 to 8 g / L, further preferably 3 to 6 g / L, and further preferably 4 to 5 g / L; in the mixture B, the mass of the first surfactant accounts for 4 to 12% of the mass of graphene oxide, further preferably 6 to 10%, and further preferably 8%.
[0040] Wherein, in step (3), the flake size of the graphene oxide is 0.01 to 20 μm; the graphene oxide can be purchased commercially or prepared using the Hummer's method.
[0041] Wherein, in step (3), the mixing is carried out by ultrasonic stirring for 10 minutes to 30 minutes.
[0042] In some embodiments, in step (4), the stirring rate of the stirring is 100 r / min to 700 r / min; the emulsification time is 10 min to 30 min; in the mixture C, the mass ratio of graphene oxide to the driver is 1:10 to 10:1; the volume ratio of the volatile solvent in the mixture A to the first surfactant solution in the mixture B is 10:90 to 90:10.
[0043] In some embodiments, preferably, in step (4), the stirring rate of the stirring is 200 r / min to 600 r / min, more preferably 300 r / min to 500 r / min, and more preferably 400 r / min; the emulsification time is 10 min to 20 min, and more preferably 15 min; in the mixture C, the mass ratio of graphene oxide to the driver is (1 to 5):1, more preferably (1 to 3):1, and more preferably 2:1; the volume ratio of the volatile solvent in the mixture A to the first surfactant solution in the mixture B is (2 to 5):(6 to 9), more preferably (2 to 4):(7 to 9), and more preferably 3:8.
[0044] In some embodiments, in step (5), the second surfactant is any one of sodium dodecyl sulfate and sodium pentadecylbenzenesulfonate or a combination of two thereof; in the second surfactant solution, the solvent is water, and the mass fraction of the second surfactant in the solution is 1% to 10%; the heating temperature is 20°C to 50°C; the stirring rate is 100r / min to 700r / min; and the stirring time is 4h to 7h.
[0045] In some embodiments, preferably, in step (5), in the second surfactant solution, the solvent is water, and the mass fraction of the second surfactant in the solution is 2% to 8%, further preferably 2% to 6%, and further preferably 4%; the heating temperature of the heating is 30°C to 50°C, and further preferably 40°C; the stirring rate of the stirring is 200r / min to 500r / min, further preferably 200r / min to 400r / min, and further preferably 300r / min to 400r / min; the stirring time of the stirring is 4h to 6h, and further preferably 4h to 5h.
[0046] In some embodiments, the mass ratio of the first surfactant used in step (3) to the second surfactant used in step (5) is 1:10 to 10:1.
[0047] In some embodiments, preferably, the mass ratio of the first surfactant used in step (3) to the second surfactant used in step (5) is (1-5): (1-6), more preferably (1-3): (2-5), and even more preferably 2:3.
[0048] Wherein, in step (5), the solid-liquid separation is carried out by centrifugation at a centrifugal speed of 3000 r / min to 9000 r / min; the washing is carried out by water for 3 to 5 times; the drying temperature is 30°C to 40°C and the drying time is 8h to 24h.
[0049] The liquid metal-based core-shell structure phase change filler prepared by the above preparation method is also within the protection scope of the present invention.
[0050] The use of the above-mentioned liquid metal-based core-shell structure phase change filler in the preparation of heat-conducting and / or energy-storing and / or temperature-regulating phase change materials is also within the protection scope of the present invention.
[0051] The present invention discloses a liquid metal-based core-shell structure phase change material with high stability, low supercooling and high thermal conductivity, including a shell-core structure composed of graphene oxide and a driver, a core material composed of porous particles filled with liquid metal and nano nucleating agents, prepared by a solvent evaporation method, and its application in high thermal conductivity phase change thermostat material. Among them, the porous particles filled with liquid metal and nano nucleating agents are prepared by a method of grinding liquid metal, nano nucleating agents and porous particles together. In the preparation process of the solvent volatilization method, the porous particles filled with liquid metal and nano nucleating agents and the driver are dispersed in a volatile solvent as an oil phase; the graphene oxide solution is dispersed in a surfactant aqueous solution as an aqueous phase; the oil phase and the aqueous phase are mixed, and a core-shell structure material of graphene oxide@loaded liquid metal and nano nucleating agent porous particles is prepared through high-speed stirring and solvent evaporation. The present invention uses a solvent evaporation method to prepare a core-shell structure material, which can be used as a phase change thermostat material filler, while achieving high stability, low supercooling and high thermal conductivity.
[0052] Beneficial effects:
[0053] (1) The present invention prepares a thermally conductive phase change filler loaded with liquid metal and nano nucleating agent, with porous particles as the core, a driving agent as the inner shell, and graphene oxide as the outer shell by a simple solvent volatilization method. The process uses a driving agent to drive graphene oxide for encapsulation, which is simple to operate and has a high loading rate.
[0054] (2) The liquid metal-based core-shell structure phase change filler provided by the present invention encompasses all liquid metals, has high phase change latent heat and high thermal conductivity, and uses a nano-nucleating agent to improve the supercooling phenomenon of the liquid metal.
[0055] (3) The liquid metal-based core-shell structure phase change filler provided by the present invention includes all porous particles as the core carrier to load the liquid metal, has a porous structure, and has a large loading amount (more than 80wt.%).
[0056] (4) The present invention uses graphene oxide material with high flexibility, density and strength as a shell material to cover porous particles, which effectively buffers the volume expansion stress generated when the liquid metal undergoes phase change and provides a highly stable phase change material structure.
[0057] (5) The present invention uses liquid metal with high thermal conductivity and high phase change latent heat as the core material to efficiently load it in the porous particles, and uses graphene oxide with good thermal conductivity as the shell material to coat the porous particles, which can greatly enhance the thermal conductivity of the filler in the composite material and improve its thermal conductivity.
[0058] (6) The liquid metal-based core-shell structure phase change filler provided by the present invention can be used in temperature control, energy storage, and heat conduction. It can simultaneously solve the problems of liquid metal leakage and overcooling, and has great application value in the field of energy storage and thermal management. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.
[0060] Figure 1 It is a schematic structural diagram of the liquid metal-based core-shell structure phase change filler of the present invention.
[0061] Figure 2 This is an optical photograph of the mesoporous silica powder used in Example 1.
[0062] Figure 3 This is an optical photograph of the silicon dioxide loaded with liquid metal gallium and nanosilver obtained in step (1) of Example 1.
[0063] Figure 4 This is an optical photograph of the graphene oxide / silicon dioxide phase change filler loaded with liquid metal gallium and nano-silver prepared in Example 1.
[0064] Figure 5 This is a scanning electron microscope image of the mesoporous silica powder used in Example 1.
[0065] Figure 6 This is a scanning electron microscope image of the graphene oxide / silicon dioxide phase change filler loaded with liquid metal gallium and nano-silver prepared in Example 1.
[0066] Figure 7 It is the DSC graph of the liquid metal gallium used in the embodiment of the present invention.
[0067] Figure 8 This is the DSC graph of the graphene oxide / silicon dioxide phase change filler loaded with liquid metal gallium and nano-silver prepared in Example 1.
[0068] Fig. 9 This is the DSC graph of the graphene oxide / silicon dioxide phase change filler loaded with liquid metal gallium and nano-aluminum oxide prepared in Example 2. DETAILED DESCRIPTION
[0069] The present invention can be better understood according to the following examples. However, it is easy for those skilled in the art to understand that the contents described in the examples are only used to illustrate the present invention, and should not and will not limit the present invention described in detail in the claims.
[0070] The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0071] The graphene oxide used in the embodiments of the present invention is prepared by Hummer's method.
[0072] Figure 1 It is a structural schematic diagram of the liquid metal-based core-shell structure phase change filler of the present invention, including a core-shell structure composed of porous material particles, a driver, and graphene oxide, and liquid metal and nano nucleating agent loaded on the core structure; wherein, the core-shell structure includes a porous material particle core, and a driver inner shell and a graphene oxide outer shell coated on the outer surface of the porous material particle core.
[0073] The determination method of the relevant parameters in the embodiment of the present invention is as follows:
[0074] (1) Latent heat of phase change: The DSC curve is obtained by measuring the sample by differential scanning calorimetry. The latent heat of phase change is the area enclosed by the DSC heat flow curve and the zero phase change latent heat equivalent baseline, which can be obtained by iterative calculation (GB / T19466.2-2004).
[0075] (2) Supercooling: It is obtained by calculating the difference between the phase transition temperature of the molten metal in the equilibrium state and the actual phase transition temperature (GB / T 19466.2-2004).
[0076] (3) Cyclic weight loss rate: It is calculated by placing the sample on filter paper and performing a cyclic heating and cooling process, and then weighing the final remaining sample mass.
[0077] (4) Thermal conductivity: The filler was added into the silicone grease at a mass fraction of 50%, and the thermal conductivity of the composite material was obtained by testing with a DRL-V thermal conductivity tester.
[0078] Embodiment 1:
[0079] (1) Mixing the heated and melted liquid metal gallium, nanosilver (size 10-30 nm) and mesoporous silica powder (diameter of silica 5 μm, pore size 30-50 nm), wherein the mass ratio of liquid metal gallium to silica is 10:1, and the mass of nanosilver accounts for 0.3% of the mass of liquid metal gallium. Grinding allows the liquid metal gallium and nanosilver to be wetted and adsorbed on the mesoporous silica microspheres. The grinding process is maintained at a temperature of 30° C. (higher than the melting point of gallium metal) by a hot stage, and finally obtaining silica powder loaded with liquid metal gallium and nanosilver;
[0080] (2) dispersing 40 mg of the silica powder loaded with liquid metal gallium and nanosilver obtained in step (1) and 20 mg of benzotriazole (the mass ratio of the two is 2:1) in 30 mL of dichloromethane solvent, stirring ultrasonically for 20 min, and mixing thoroughly to obtain a mixture A;
[0081] (3) preparing a graphene oxide aqueous solution (concentration of 4.5 g / L) by Hummer's method; adding 8.89 mL of the obtained graphene oxide aqueous solution (containing 40 mg of graphene oxide, and the mass ratio of graphene oxide to benzotriazole in the graphene oxide aqueous solution is 2:1) into 80 mL of a sodium dodecyl sulfate aqueous solution (4 wt.%), stirring with ultrasound for 10 min, and mixing thoroughly to obtain a mixture B;
[0082] (4) under mechanical stirring at 400 r / min, slowly adding the mixture A obtained in step (2) to the mixture B obtained in step (3), stirring for 15 minutes after the dropwise addition for emulsification, to obtain a mixture C;
[0083] (5) Add 120 mL of sodium dodecyl sulfate aqueous solution (4 wt.%) to the mixture C obtained in step (4), heat in a water bath at 40° C., and mechanically stir at 350 r / min for 4 h to fully evaporate the dichloromethane solvent, wash and centrifuge at 5000 r / min for 3 times, and dry in an oven at 40° C. for 12 h to obtain a graphene oxide / silicon dioxide phase change filler loaded with liquid metal gallium and nano-silver.
[0084] Figure 2 This is an optical photograph of the mesoporous silica powder used in Example 1, which appears as a white powder.
[0085] Figure 3This is an optical photograph of the silicon dioxide loaded with liquid metal gallium and nano-silver obtained in step (1) of Example 1; due to the adsorption loading of liquid metal gallium, the material has a silver-gray powder appearance and a metallic luster.
[0086] Figure 4 This is an optical photograph of the graphene oxide / silicon dioxide phase change filler loaded with liquid metal gallium and nano-silver finally prepared in step (5) of Example 1; since the outer surface is coated with graphene oxide, the appearance of the material is dark brown-gray without obvious metallic luster.
[0087] Figure 5 This is a scanning electron microscope image of the mesoporous silica powder used in Example 1; the silica is spherical and uniform in size, with a spherical diameter of 5 μm; the silica surface has uniform and evenly distributed pores, with a size of about 30 to 50 nm; the surface has been hydrophobically modified with oleic acid.
[0088] Figure 6 This is a scanning electron microscope image of the graphene oxide / silicon dioxide phase change filler loaded with liquid metal gallium and nano-silver finally prepared in step (5) in Example 1; it can be clearly seen from the electron microscope image that the graphene oxide is completely wrapped on the surface of the silicon dioxide microspheres, proving that the graphene oxide / silicon dioxide shell-core structure phase change filler loaded with liquid metal gallium and nano-silver is successfully prepared.
[0089] Figure 7 It is the DSC graph of the liquid metal gallium used in Example 1; it is known that the melting point of metal gallium is 29.76°C. It can be seen from the figure that the peak temperature of the exothermic peak in the DSC curve of pure liquid metal gallium in the present invention is -9.78°C, the peak temperature of the endothermic peak is 30.25°C, the supercooling degree is -39.54°C, and the latent heat of phase change is about 88.47 kJ / kg.
[0090] Figure 8 This is the DSC graph of the graphene oxide / silicon dioxide phase change filler loaded with liquid metal gallium and nanosilver finally prepared in step (5) of Example 1; it can be seen from the figure that an exothermic peak appears in the cooling and solidification process in the curve, and the peak temperature is 6.58°C, the supercooling degree is -23.18°C, and the phase change latent heat is about 79.9 kJ / kg. It can be seen that the phase change filler prepared by the present invention effectively improves the supercooling phenomenon of liquid metal and maintains a relatively high phase change latent heat.
[0091] Embodiment 2:
[0092] (1) Mixing the heated and melted liquid metal gallium, nano-alumina (size 80-90 nm) and mesoporous silica powder (diameter of silica 30 μm, pore size 1-2 μm), wherein the mass ratio of liquid metal gallium to silica is 9:1, and the mass of nano-alumina accounts for 0.3% of the mass of liquid metal gallium. Grinding allows the liquid metal gallium and nano-alumina to be wetted and adsorbed on the mesoporous silica. The grinding process is maintained at a temperature of 30°C (higher than the melting point of gallium metal) by a hot plate, and finally obtaining silica powder loaded with liquid metal gallium and nano-alumina;
[0093] (2) dispersing 40 mg of the silica powder loaded with liquid metal gallium and nano-alumina obtained in step (1) and 20 mg of benzotriazole (the mass ratio of the two is 2:1) in 30 mL of dichloromethane solvent, stirring ultrasonically for 20 min, and mixing thoroughly to obtain a mixture A;
[0094] (3) preparing a graphene oxide aqueous solution (concentration of 4.5 g / L) by Hummer's method; adding 8.89 mL of the obtained graphene oxide aqueous solution (containing 40 mg of graphene oxide, and the mass ratio of graphene oxide to benzotriazole in the graphene oxide aqueous solution is 2:1) into 80 mL of a sodium dodecyl sulfate aqueous solution (4 wt.%), stirring with ultrasound for 10 min, and mixing thoroughly to obtain a mixture B;
[0095] (4) under mechanical stirring at 400 r / min, slowly adding the mixture A obtained in step (2) to the mixture B obtained in step (3), stirring for 15 minutes after the dropwise addition for emulsification, to obtain a mixture C;
[0096] (5) Add 120 mL of sodium dodecyl sulfate solution (4 wt.%) to the mixture C obtained in step (4), heat in a water bath at 40° C., and mechanically stir at 350 r / min for 4 h to fully evaporate the dichloromethane solvent, wash and centrifuge at 6000 r / min for 3 times, and dry in an oven at 40° C. for 12 h to obtain a graphene oxide / silicon dioxide phase change filler loaded with liquid metal gallium and nano-alumina.
[0097] Fig. 9 This is the DSC graph of the graphene oxide / silicon dioxide phase change filler loaded with liquid metal gallium and nano-alumina prepared in Example 2; it can be seen from the figure that an exothermic peak appears in the cooling and solidification process in the curve, and the peak temperature is 7.24°C, the supercooling degree is -22.52°C, and the phase change latent heat is about 78kJ / kg. It can be seen that the graphene oxide / silicon dioxide phase change filler loaded with liquid metal gallium and nano-alumina prepared in Example 2 can improve the supercooling phenomenon of liquid metal and maintain a relatively high phase change latent heat.
[0098] Embodiment 3:
[0099] (1) Mixing the heated and melted gallium-indium-based liquid metal (gallium-indium mass ratio of 4:1), nano-magnesium oxide (size of 70 nm) and porous carbon (size of 1-10 μm, pore size of 300 nm) powder, wherein the mass ratio of gallium-indium-based liquid metal to porous carbon is 8:1, and the mass of nano-magnesium oxide accounts for 0.3% of the mass of gallium-indium-based liquid metal. Grinding allows the gallium-indium-based liquid metal and nano-magnesium oxide to be wetted and adsorbed on the porous carbon, and the grinding process is maintained at a temperature of 40° C. on a hot stage, and finally obtaining carbon powder loaded with gallium-indium-based liquid metal and nano-magnesium oxide;
[0100] (2) dispersing 40 mg of the carbon powder loaded with gallium-indium-based liquid metal and nano-magnesium oxide obtained in step (1) and 20 mg of benzotriazole (the mass ratio of the two is 2:1) in 30 mL of dichloromethane solvent, stirring ultrasonically for 20 min, and mixing thoroughly to obtain a mixture A;
[0101] (3) preparing a graphene oxide aqueous solution (concentration of 4.5 g / L) by Hummer's method; adding 8.89 mL of the obtained graphene oxide aqueous solution (containing 40 mg of graphene oxide, and the mass ratio of graphene oxide to benzotriazole in the graphene oxide aqueous solution is 2:1) into 80 mL of a sodium dodecyl sulfate aqueous solution (4 wt.%), stirring with ultrasound for 10 min, and mixing thoroughly to obtain a mixture B;
[0102] (4) under the condition of mechanical stirring at 400 r / min, the mixture A obtained in step (2) was slowly added to the mixture B obtained in step (3), and after the dropwise addition was completed, the mixture was stirred for 15 minutes for emulsification to obtain a mixture C;
[0103] (5) Add 120 mL of sodium dodecyl sulfate solution (4 wt.%) to the mixture C obtained in step (4), heat in a water bath at 40° C., and mechanically stir at 350 r / min for 4 h to fully evaporate the dichloromethane solvent, wash and centrifuge at 8000 r / min for 3 times, and dry in an oven at 40° C. for 12 h to obtain a graphene oxide / carbon phase change filler loaded with gallium-indium-based liquid metal and nano-magnesium oxide.
[0104] Comparative Example 1: No addition of graphene oxide
[0105] (1) Mixing the heated and melted liquid metal gallium, nanosilver (size 10-30 nm) and mesoporous silica powder (diameter of silica 5 μm, pore size 30-50 nm), wherein the mass ratio of liquid metal gallium to silica is 9:1, and the mass of nanosilver accounts for 0.3% of the mass of liquid metal gallium. Grinding allows the liquid metal gallium and nanosilver to be wetted and adsorbed on the silica microspheres, and the grinding process is maintained at a temperature of 30° C. on a hot stage, and finally obtaining silica powder loaded with liquid metal gallium and nanosilver;
[0106] (2) dispersing 40 mg of the silica powder loaded with liquid metal gallium and nanosilver obtained in step (1) and 20 mg of benzotriazole (the mass ratio of the two is 2:1) in 30 mL of dichloromethane solvent, stirring ultrasonically for 20 min, and mixing thoroughly to obtain a mixture A;
[0107] (3) The mixture A was centrifuged at a speed of 8000 r / min and dried in an oven at 40° C. for 12 h to obtain a silicon dioxide phase change material loaded with liquid metal gallium and nano-silver.
[0108] Comparative Example 2: No nano nucleating agent added
[0109] (1) adding the heated and melted liquid metal gallium to mesoporous silica powder (diameter of silica: 5 μm, pore size: 30-50 nm) at a mass ratio of 10:1, and grinding the liquid metal gallium to allow it to be wetted, adsorbed and loaded in the mesoporous silica. The grinding process was maintained at a temperature of 30° C. on a hot plate, and finally obtaining silica powder loaded with liquid metal gallium;
[0110] (2) dispersing 40 mg of the silica powder loaded with liquid metal gallium obtained in step (1) and 20 mg of benzotriazole (mass ratio of 2:1) in 30 mL of dichloromethane solvent, stirring ultrasonically for 20 min, and mixing thoroughly to obtain a mixture A;
[0111] (3) preparing a graphene oxide aqueous solution (concentration of 4.5 g / L) by Hummer's method; adding 8.89 mL of the obtained graphene oxide aqueous solution (containing 40 mg of graphene oxide, and the mass ratio of graphene oxide to benzotriazole in the graphene oxide aqueous solution is 2:1) into 80 mL of a sodium dodecyl sulfate aqueous solution (4 wt.%), stirring with ultrasound for 10 min, and mixing thoroughly to obtain a mixture B;
[0112] (4) under mechanical stirring at 400 r / min, slowly adding the mixture A obtained in step (2) to the mixture B obtained in step (3), stirring for 15 minutes after the dropwise addition for emulsification, to obtain a mixture C;
[0113] (5) Add 120 mL of sodium dodecyl sulfate solution (4 wt.%) to the mixture C obtained in step (4), heat in a water bath at 40° C., and mechanically stir at 350 r / min for 4 h to fully evaporate the dichloromethane solvent, wash and centrifuge at 8000 r / min for 3 times, and dry in an oven at 40° C. for 12 h to obtain a graphene oxide / silicon dioxide phase change filler loaded with liquid metal gallium.
[0114] Example 4: Performance Characterization of Phase Change Fillers
[0115] Table 1 shows the phase change latent heat, supercooling, cycle weight loss rate and thermal conductivity of different liquid metal phase change fillers prepared in Examples 1 to 3 and Comparative Examples 1 to 2.
[0116] from Figure 7 It can be seen that the peak temperature of the exothermic peak in the DSC curve of pure liquid gallium is -9.78°C, the peak temperature of the endothermic peak is 30.25°C, the supercooling is -39.54°C, and the latent heat of phase change is about 88.47 kJ / kg. (1) Since other materials such as porous particles are not phase change materials themselves, there is no latent heat of phase change; therefore, it can be judged from the latent heat data of phase change of various embodiments and comparative examples that the loading amount of liquid metal in porous particles is very high; (2) Nano nucleating agents are added to embodiments 1 to 3 and comparative example 1. From the comparison of supercooling data, it can be seen that the addition of nano nucleating agents can effectively improve the supercooling phenomenon of liquid metal; (3) The present invention repeats the heating and cooling process for 10 cycles and then weighs and calculates its weight loss rate to explore the stability of the filler structure. By comparing the weight loss rates of embodiments 1 to 3, comparative example 2 and comparative example 1, it can be found that the weight loss rate of comparative example 1 is very high, which shows that the use of graphene oxide wrapping can effectively seal liquid metal and prevent it from leaking. During the heating and cooling process, the liquid metal will undergo a phase change, resulting in a volume difference. Graphene oxide has good flexibility and strength, and can effectively buffer the stress caused by volume expansion, ensuring that the core-shell structure of the filler is not damaged, making it very stable. (4) The thermal conductivity of the organic silicone grease used in the present invention is 0.5W / mK; by analyzing the thermal conductivity of the organic silicone grease composite material used as filler in each embodiment and comparative example, it can be found that the addition of filler greatly improves the thermal conductivity of the composite material, and it is a high thermal conductivity phase change filler.
[0117] Table 1 Phase change latent heat, supercooling and cyclic weight loss rate of different liquid metal phase change fillers
[0118]
[0119]
[0120] The present invention provides a liquid metal-based core-shell structure phase change filler and its preparation method and application ideas and methods. There are many methods and ways to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, several improvements and modifications can be made, and these improvements and modifications should also be regarded as the scope of protection of the present invention. All components not specified in this embodiment can be implemented by existing technologies.
Claims
1. A liquid metal-based core-shell structure phase change filler, characterized in that: It includes a core, an inner shell, and an outer shell; Wherein, the core is a porous material, and the core is used as a carrier to load the liquid metal and the nano nucleating agent; The inner shell is coated on the outer surface of the inner core, and the inner shell is a driving agent; The outer shell is coated on the outer surface of the inner shell, and the outer shell is graphene oxide.
2. The liquid metal-based core-shell structure phase change filler according to claim 1, characterized in that: The porous material is any one of mesoporous silica and porous carbon or a combination of the two; The liquid metal is any one or a combination of gallium, indium, bismuth, cesium and rubidium; The nano nucleating agent is any one or a combination of nano copper, nano silver, nano magnesium oxide, nano aluminum oxide and nano silicon oxide; The driving agent is any one of benzotriazole and 2-(2'-hydroxy-3',5'-dipentylphenyl)benzotriazole or a combination of the two.
3. The method for preparing the liquid metal-based core-shell structure phase change filler according to claim 1 or 2, characterized in that: The steps include: (1) mixing liquid metal, nano-nucleating agent and porous material, and grinding to obtain a porous material loaded with liquid metal and nano-nucleating agent; (2) dispersing the porous material loaded with liquid metal and nano nucleating agent obtained in step (1) and the driving agent in a volatile solvent, and mixing them to obtain a mixture A; (3) preparing a graphene oxide solution; adding the graphene oxide solution to the first surfactant solution and mixing to obtain a mixture B; (4) adding the mixture A obtained in step (2) to the mixture B obtained in step (3) under stirring, stirring and emulsifying, to obtain a mixture C; (5) adding a second surfactant solution to the mixture C obtained in step (4), stirring under heating conditions to allow the volatile solvent to fully evaporate, separating the solid from the liquid, washing the solid, and drying to obtain a liquid metal-based core-shell structure phase change filler.
4. The preparation method according to claim 3, characterized in that: In step (1), the mass ratio of the liquid metal to the porous material is 1:10 to 10:1; the mass of the nano nucleating agent accounts for 0.1% to 1.0% of the mass of the liquid metal.
5. The preparation method according to claim 3, characterized in that: In step (2), the volatile solvent is any one of dichloromethane, chloroform, xylene, acetone and dimethyl ether or a combination of several thereof; the driving agent is any one of benzotriazole and 2-(2'-hydroxy-3',5'-dipentylphenyl)benzotriazole or a combination of two thereof; and the mass ratio of the porous material loaded with liquid metal and nano nucleating agent to the driving agent is 1:10 to 10:
1.
6. The preparation method according to claim 3, characterized in that: In step (3), the first surfactant is any one of sodium dodecyl sulfate and sodium pentadecylbenzenesulfonate or a combination of both; in the first surfactant solution, the solvent is water, and the mass fraction of the first surfactant in the solution is 1% to 10%; in the graphene oxide solution, the solvent is water, and the concentration of graphene oxide in the solution is 1 to 13 g / L; in the mixture B, the mass of the first surfactant accounts for 3 to 12% of the mass of the graphene oxide.
7. The preparation method according to claim 3, characterized in that: In step (4), the stirring rate of the stirring is 100 r / min to 700 r / min; the emulsification time is 10 min to 30 min; in the mixture C, the mass ratio of graphene oxide to the driver is 1:10 to 10:1; the volume ratio of the volatile solvent in the mixture A to the first surfactant solution in the mixture B is 10:90 to 90:
10.
8. The preparation method according to claim 3, characterized in that: In step (5), the second surfactant is any one of sodium dodecyl sulfate and sodium pentadecylbenzenesulfonate or a combination of the two; in the second surfactant solution, the solvent is water, and the mass fraction of the second surfactant in the solution is 1% to 10%; the heating temperature is 20° C. to 50° C.; the stirring rate is 100 r / min to 700 r / min; and the stirring time is 4 h to 7 h; The mass ratio of the first surfactant used in step (3) to the second surfactant used in step (5) is 1:10 to 10:
1.
9. Liquid metal-based core-shell structure phase change filler prepared by the preparation method according to any one of claims 3 to 8.
10. Use of the liquid metal-based core-shell structure phase change filler according to claim 1 or 9 in the preparation of heat-conducting and / or energy-storing and / or temperature-regulating phase change materials.
